UTILISATION OF CASSAVA PEELS FERMENTED WITH OIL PALM SLURRY AS FEED IN THE DIET OF WEST AFRICAN DWARF SHEEP (2016)
Shortage of pasture during dry season militates against production of grazing animals in Nigeria. Cassava Peels (CaP) and Oil Palm Slurry (OPS) are agro-industrial by-products obtainable throughout the year. Utilization of CaP as feed can be enhanced through fermentation with OPS. However, there is dearth of information on the use of fermented CaP as feedstuff for West African Dwarf (WAD) sheep. The use of CaP fermented with OPS as feed for WAD sheep was therefore investigated. Samples of OPS randomly obtained from Ikoyi, Badeku, Mamu and Benin in South Western Nigeria and CaP were analysed for their dry matter (DM), and proximate (Crude Protein (CP), Crude Fibre (CF), Ether Extract (EE) and fibre (Neutral Detergent Fibre (NDF), Acid Detergent Fibre (ADF), Acid Detergent Lignin (ADL), cellulose and hemicelluloses) compositions. One litre of OPS was mixed with 1Kg, 2Kg, 3Kg, 4Kg, 5Kg (Diets A – E) of CaP, respectively while 6Kg (Diet F) of CaP only served as the control. The diets were fermented for five days in air-tight cellophane bags, sun-cured and analysed for proximate and fibre contents. Eighteen WAD sheep were allocated to the six treatments in triplicate using completely randomised design and each group was fed ad libitum for 14days. Samples of rumen liquor were collected for in vitro Gas Production (IVGP) to predict the Potential Degradability (PD), Insoluble Degradable Fraction (IDF), Rate of Gas Production (RGP), Organic Matter Digestibility (OMD), Metabolisable Energy (ME), Short Chain Fatty Acids (SCFA), pH and ammonia-N (NH3-N) for 96 hours at 3 hours interval. The pre prandia and 3, 6 and 9 hours post prandia samples of rumen liquor were collected for microbial count in a 4x6 factorial arrangement. Data were analysed using ANOVA (p=0.05) The OPS from Mamu had the highest DM (43.2%), CP (8.2%), EE (6.5%) and CF (8.0%). The CF and EE obtained for the fermented diets decreased with CaP inclusion (4.7 to 3.7% and 10.0 to 7.5%) in diets A and E respectively. Similar decreasing values for ADF (40.2-30.2), NDF (59.0-48.0), ADL (20.2-18.0), Cellulose (20.7-12.3) and hemicellulose (22.0-18.0) contents were obtained due to fermentation. The IDF value was significant for diets A (39.3) and F (47.0) at 24hours and for other treatments at 60 hours. The PD estimates varied significantly from 73.5 in diet E to 98.5 in diet B at 60 hours. The RGP increased with time at all observed hours. The pH value (6.21) was significant at 60 hours. Estimated ME, OMD and SCFA were highest for diet B with values of 11.4, 83.0 and 1.6 respectively. The LogCFU of all treatments pre-prandial was between 5.0 and 5.3. Apparent interaction between 0-9 hours for pH and NH3-N were not significant. The combination of three parts of cassava peels fermented with one part of oil palm slurry from Mamu for five days and sun-cured was best as supplement for grazing West African dwarf sheep